Expectation-Based Loss Aversion and Strategic Interaction - Simon Dato; Daniel Müller; Andreas Grunewald (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper provides a comprehensive analysis regarding strategic interaction under expectation-based loss-aversion. First, we develop a coherent framework for the analysis by extending the equilibrium concepts of K szegi and Rabin (2006, 2007) to strategic interaction and demonstrate how to derive equilibria. Second, we delineate how expectation-based loss-averse players differ in their strategic behavior from their counterparts with standard expected-utility preferences. Third, we analyze equilibrium play under expectation-based loss aversion and comment on the existence of equilibria.
Keywords: C72; D03; D81; 330